Influence of different ester side groups in polymers on the vapor phase infiltration with trimethyl aluminum - Mai, Lukas; Maniar, Dina; Zysk, Frederik; Schobel, Judith; Kühne, Thomas D.; Loos, Katja; Devi, Anjana (Dalton Transactions, 2022)
The vapor phase infiltration (VPI) process of trimethyl aluminum (TMA) into poly(4-acetoxystyrene) (POAcSt), poly(nonyl methacrylate) (PNMA) and poly(tert-butyl methacrylate) (PtBMA) is reported. Depth-profiling X-ray photoelectron spectroscopy (XPS) measurements are used for the first time for VPI based hybrid materials to determine the aluminum content over the polymer film thickness. An understanding of the reaction mechanism on the interaction of TMA infiltrating into the different polymers was obtained through infrared (IR) spectroscopy supported by density functional theory (DFT) studies. It is shown that the loading with aluminum is highly dependent on the respective ester side group of the used polymer, which is observed to be the reactive site for TMA during the infiltration. IR spectroscopy hints that the infiltration is incomplete for POAcSt and PNMA, as indicated by the characteristic vibration bands of the aluminum coordination to the carbonyl groups within the polymers. In this context, two different reaction pathways are discussed. One deals with the formation of an acetal, the other is characterized by the release of a leaving group. Both were found to be in direct concurrence dependent on the polymer side group as revealed by DFT calculations of the IR spectra, as well as the reaction energies of two possible reaction paths. From this study, one can infer that the degree of infiltration in a VPI process strongly depends on the polymer side groups, which facilitates the choice of the polymer for targeted applications.
CRIS-Team Scopus Importer:2023-03-20